FAKTOR-FAKTOR YANG MEMPENGARUHI KEUNTUGAN USAHATANI MELON DI DESA KREJENGAN KEC. KREJENGAN KAB. PROBOLINGGO - Anita Wulandari; Masyhuri Machfudz; Farida Syakir (Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2020)
This study aims to 1) To determine of efficiency of melon farming in Krejengan Village. 2) To analyze the factors that influence the profitability of melon farming in Krejengan Village. The research method used is descriptive and quantitative methods with sampling methods using the random sampling. Analysis of the data used is the Cobb Douglass profit function with the Unit Output Price technique or UOP of Cobb Douglass Profit Function (UOP-CDPF). The study obtained the results that: 1) The results of the study note the benefits of melon farming of Rp. 12,351,858.29 per hectare every planting and R / C Ratio of 2.33, that melon farming in Krejengan Village is profitable and efficient. 2) The results of multiple regression analysis of Cobb Douglass profit function model, independent variables that affect profit is land area, the price of seeds, the price of urea, and the price of drugs at a 90% confidence level. While the independent variables that do not affect profit are the age variable, the price of organic fertilizer, the price of phonska fertilizer, labor.